Field Evaluation of Cholkit Rapid Diagnostic Test for Vibrio Cholerae O1 During a Cholera Outbreak in Malawi, 2018. (16th October 2020) - Chibwe, Innocent; Kasambara, Watipaso; Kagoli, Mathews; Milala, Harry; Gondwe, Charity; Azman, Andrew S
Abstract: Rapid diagnostic tests (RDTs) for cholera are an important emerging tool for surveillance, yet the currently available tests have several limitations. We assess the performance of a new RDT, Cholkit, during a cholera outbreak in Malawi compared with culture and find a sensitivity of 93.0% (95% CI, 83.0%–98.1%) and a specificity of 95.7% (95% CI, 78.1%–100.0%).